Micromechanical modeling of the interfacial zone in hot mix asphalt through use of a heterogeneous numerical method. Issue 11 (18th September 2020) - EL Haloui, Yassine; Hajikarimi, Pouria; Fakhari Tehrani, Fateh; Absi, Joseph; El Omari, Mohamed; Petit, Christophe
Abstract: This work focuses on the use of a heterogeneous generation method in order to develop a micromechanical model of Hot Mix Asphalt (HMA) that takes into account the effects of characteristics at the interfacial zone (IZ), where aggregate surfaces come into contact with the mortar matrix. Numerical calculations are conducted to investigate the effect of IZ mechanical characteristics on both the overall viscoelastic response of HMA and the local scale behavior. First of all, the HMA is treated as a biphasic material composed of mortar and granular inclusions. Next, a third phase is added between these two at each point of aggregate/mortar contact. Elastic and viscoelastic behaviors are assigned to the aggregates and mortar, respectively. The mechanical behavior of IZ varies between that of the inclusions and the matrix. At the global scale, these numerical results demonstrate that the use of triphasic micromechanical models improves the predictive accuracy of the dynamic modulus. At the local scale, a significant strain variation was found in each model. These results justify our triphasic modeling approach whenever local zone characteristics are the subject of interest.